A Model for Running Effective Educational Scavenger Hunts During Campus Orientation to Onboard new University Students. - Zachary Fitz-Walter; Nicholas O’Donnell; Joshua Hall; Henry Sun; Justin Carter (Student Success, 2025)
University orientation plays a crucial role in fostering student engagement, social integration, and retention. This practice report describes the development and refinement of a game-based orientation activity: a digital scavenger hunt designed to enhance engagement, social connectedness, and campus familiarisation. The activity was guided by the ENGAGE framework, a practical six-stage model for creating effective scavenger hunts. Over three years (2023 to 2025), it was iteratively improved based on participant feedback and evaluated using the MEEGA+ game evaluation framework. Feedback highlighted strong outcomes in social interaction, campus exploration, and enjoyment. Importantly, the initiative demonstrates how game-based activities can be scaled across years with minimal staff input. This report shares lessons learned and presents a practical, low-effort, and effective model that other institutions can adapt to improve student transitions and success through engaging, game-based orientation experiences.